Building shock-responsive national social protection systems in the Middle East and North Africa (MENA) region. Executive summary - Raquel Tebaldi (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
The Middle East and North Africa (MENA) region is confronted by significant challenges resulting from multiple shocks and complex emergencies: countries in the region face various risks in terms of natural disasters, including earthquakes, floods and drought; violent conflicts, such as in Syria, pose unprecedented challenges related to the scale of human displacement; and the breakdown of service provision caused by conflict is leading to the increasing prevalence of malnutrition and communicable diseases in Yemen.
Keywords: 330; Building; Shock-Responsive; National; Social Protection; Systems; Middle East; North Africa; MENA